2022
DOI: 10.1021/acs.cgd.2c00215
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nucleated Nonpolar GaN Nanowires with Strong and Enhanced UV Luminescence

Abstract: Compared with polar c-axis GaN, nonpolar GaN crystals with different orientations show distinct optical and electrical properties and thus some promising and functional applications can be expected. In this work, we report the self-assembled nucleation and synthesis of nonpolar GaN nanowires through a conventional chemical vapor deposition approach and systematic investigation of their microstructures and crystallography using a high-resolution transmission electron microscope. Comparative optical studies on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In recent studies, nonpolar GaN nanowires have shown unique optical and electrical properties. Liu and co-workers 8 synthesized nonpolar a-plane GaN nanowires through a conventional CVD process and found that nonpolar GaN nanowires have superior crystallinity and excellent luminescence property. Xiao et al 16 have identified the significance of the nonpolar GaN planes in promoting the PEC hydrogen evolution reaction through a combination of theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, nonpolar GaN nanowires have shown unique optical and electrical properties. Liu and co-workers 8 synthesized nonpolar a-plane GaN nanowires through a conventional CVD process and found that nonpolar GaN nanowires have superior crystallinity and excellent luminescence property. Xiao et al 16 have identified the significance of the nonpolar GaN planes in promoting the PEC hydrogen evolution reaction through a combination of theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in electronegativity leads to the formation of electric dipoles, which in turn results in spontaneous polarization. In order to avoid/overcome the polarization effect caused by the polar GaN, the research focusing on the growth of nonpolar GaN is gradually increasing, with one-dimensional nanomaterials being a significant component. One-dimensional nanomaterials such as nanowires and nanorods are considered as promising candidates for next-generation high-performance devices because of their huge surface–volume ratio and highly regulable structure compared to bulk GaN crystal materials. , Various growth techniques have been applied to the growth of nonpolar GaN nanowires, including metal-catalyzed metal-organic chemical vapor deposition (MOCVD), direct nitridation/vapor transport, , and catalyst-free selective-area molecular beam epitaxy (SA-MBE) . And among the increasingly sophisticated preparation systems, the convenient chemical vapor deposition (CVD) method is one representative of the ways to prepare nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation